Implementasi Algoritma Profile Matching Untuk Kelayakan Ujian Pada Universitas Handayani Makassar - Andi Alamsyah; Najirah Umar; M Adnan Nur (Prosiding SISFOTEK, 2023)
The 1945 Constitution guarantees equal education for all Indonesian citizens, but 12 years of compulsory education is still not enough to cope with the increasing demands of the labor market. This makes it difficult for the younger generation to find jobs that match their expectations. Handayani University Makassar plays a role in helping to overcome these problems. Currently, the process of determining college eligibility is still manual and complicated. This research proposes a solution using technology through profile matching on web applications. This method determines test eligibility based on predetermined attribute weights. This helps students assess their potential before registering for the exam. The application of profile matching algorithm will also help universities identify students who are likely to pass the exam. This will speed up decision-making and improve student progression and learning outcomes. This research aims to predict students' exam eligibility using the profile match method. So that it is expected to help students achieve maximum passing standards and complete their studies on time. The application of the profile match algorithm is also expected to overcome the problem of slow decision making, help identify outstanding students, and improve student development and learning outcomes. Therefore, this research is titled "Implementation of profile comparison algorithm to assess exam eligibility".